Post a New Question

Maths

posted by .

I have a maths exam tomorrow and am studying with a friend. We are working on a question and are getting two different answers. Could you please show us the right way to do it?

2(4x + 3)(4x - 3) - (4x + 3)squared

p.s i couldn't find a squared symbol so only the last bracket is squared, not the whole equation.

  • Maths -

    2(4x + 3)(4x - 3) - (4x + 3)squared
    we usually write it this way

    2(4x + 3)(4x - 3) - (4x + 3)^2
    = 2(16x^2 - 9) - (4x + 3)(4x + 3)
    = 2(16x^2 - 9) - (16x^2 + 24x + 9)
    = 32x^2 - 18 - 16x^2 - 24x - 9
    = 16x^2 24x - 27

    or you could take out a common factor from
    2(4x + 3)(4x - 3) - (4x + 3)^2
    = (4x + 3)(2(4x-3) - (4x+3))
    = (4x+3)(8x-6-4x-3)
    = (4x+3)(4x-9)
    = 16x^2 - 36x + 12x - 27
    = 16x^2 - 24x - 27

    not saying the second way is any easier, just another way to show it

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question